Librarian Representation in the Film Summer Strike 2022 - Putri, Ida Agusyah (UIN Raden Intan Lampung, 2023)
This article discusses the depiction of the film Summer Strike which shows the librarian profession. The aim of the research is to determine the professional competence of librarians and the personal competence of librarians depicted in the film Summer Strike. This research uses a qualitative descriptive research type with Roland Barthes' semiotic study approach by revealing denotative, connotative and mystical levels of meaning. The results of the research illustrate the representation of the professional competence of librarians depicted in the film Summer Strike as librarians who are skilled and expert in caring for libraries and their contents including selection, processing of library materials, preservation, and expertise in the field of technology. The Summer Strike film also explains librarians' knowledge of the contents of papers and librarians can channel their knowledge to readers so that librarians can be said to be intellectual actors. The Summer Strike film shows that librarians are not only experts in the field of library science, but can also research expertise in other fields. The representation of personal competence depicted in the film Summer Strike is the personality of a librarian who is too closed. This does not reflect the basic attitude of librarians in implementing the code of ethics. The librarians in this film also quickly realized and improved their librarian service attitudes so that the image of librarians was positive. The Summer Strike film also depicts librarians' attentive and caring attitude towards library users and materials. Keywords:Librarian, Librarian Competency; Roland Barthes Semiotics, Representation